2009
DOI: 10.2337/db09-0228
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effects of Genetic Variation in GCK and G6PC2 on Insulin Secretion and Fasting Glucose

Abstract: OBJECTIVEGlucokinase (GCK) and glucose-6-phosphatase catalytic subunit 2 (G6PC2) regulate the glucose-cycling step in pancreatic β-cells and may regulate insulin secretion. GCK rs1799884 and G6PC2 rs560887 have been independently associated with fasting glucose, but their interaction on glucose-insulin relationships is not well characterized.RESEARCH DESIGN AND METHODSWe tested whether these variants are associated with diabetes-related quantitative traits in Mexican Americans from the BetaGene Study and attem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
41
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(53 citation statements)
references
References 48 publications
11
41
1
Order By: Relevance
“…These observations in G6pc2 KO mice are consistent with earlier human GWAS data showing no association between G6PC2 and glucose tolerance [6972]. GWAS data also showed that G6PC2 is not associated with variations in insulin sensitivity in humans [6972], an observation that was confirmed in G6pc2 KO mice [28].…”
Section: Human Gwas Data Provide Novel Insights Into the Influence Ofsupporting
confidence: 89%
See 1 more Smart Citation
“…These observations in G6pc2 KO mice are consistent with earlier human GWAS data showing no association between G6PC2 and glucose tolerance [6972]. GWAS data also showed that G6PC2 is not associated with variations in insulin sensitivity in humans [6972], an observation that was confirmed in G6pc2 KO mice [28].…”
Section: Human Gwas Data Provide Novel Insights Into the Influence Ofsupporting
confidence: 89%
“…GWAS data also showed that G6PC2 is not associated with variations in insulin sensitivity in humans [6972], an observation that was confirmed in G6pc2 KO mice [28]. …”
Section: Human Gwas Data Provide Novel Insights Into the Influence Ofmentioning
confidence: 99%
“…With regard to diabetes-related traits, there are also some previous reports indicating an association between this polymorphism and Fasting Plasma Glucose (FPG) 21,27 or low cell function (mainly in Japanese subjects) 12,[27][28][29] . However, these findings are challenged by those of other studies 12,24,[30][31][32] and so are not consistent. Furthermore, previous studies have failed to find any significant effect of this polymorphism on insulin secretion 20,24 .…”
Section: Allelescontrasting
confidence: 55%
“…No studies have reported on the contribution of the polymorphisms to racial/ethnic differences in GDM in U.S. populations. The BetaGene study has found a link between polymorphisms of GCK and G6PC2 and impaired insulin secretion among MexicanAmerican women with histories of GDM and Finns with a similar impairment (159). In addition, the BetaGene study found a link between polymorphisms in IGF2BP2 (160), TCF7L2 (161), PPARG2 (162), and HNF4A (162) and altered insulin sensitivity in women with histories of GDM.…”
Section: Geneticsmentioning
confidence: 97%